THE STRUCTURE OF INCOME AND EXPENDITURES OF THE POPULATION OF KAZAKHSTAN - Kazhyken Meiram Zekeshuly; Satpayeva Z. T (Scientific Journal of Pedagogy and Economics, 2019)
This article is devoted to the analysis ofmonetary incomes and expenditures structure of the population of Kazakhstan. Statistical database of the Committee on Statistics of the Ministry of National Economy of the Republic of Kazakhstan served as an information base. The analysis revealed an increase in per capita nominal and real monetary incomes of the population of Kazakhstan. However, despite of falling of the share of income from labor activities, there is also an increase, while the share of social transfers is increasing. There is an increase in the differentiation of the population by income, especially the most pronounced in rural areas, while the gap in indicators between the city and the rural areas only grows. The purchasing power of the population is also declining. The main item of expenditures of the population is consumer spending, while its share in the structure of cash expenditures of the population is growing. Directions are proposed for improving the methodology for determining the cost of living.